MUATAN NILAI MULTIKULTURAL PADA BUKU TEKS SEJARAH KELAS X: SEBUAH ANALISIS WACANA - Armiyati, Laely (Universitas Sultan Ageng Tirtayasa, 2024)
Multicultural conflict become a big challenge for Indonesia. Even though it is not as extreme as in the early 2000s, conflict due to differences can still be felt in other forms, for example bullying. Therefore, multicultural education needs to be strengthened. This research aims to analyze the internalization of multicultural values in the history textbook for class X Merdeka Curriculum. The research method uses discourse analysis which consists of text analysis, discourse practice, and social praxis. The research results show that the content of multicultural values in history textbooks includes the values of identity, diversity and pluralism, and social justice. The identity value displayed is identity as a multicultural nation with natural and cultural riches. It is also implied when discussing Muhammad Hatta and Ki Hadjar as individuals with global and nationalist views. The values of diversity and pluralism are found in texts about the sasi tradition which contain the understanding that each region has its norms and traditions. Meanwhile, the value of social justice also appears in discussions about inspirational figures and articles entitled Women's World Magazine. The content of multicultural values in the history textbook for class X in the Merdeka Curriculum needs to be strengthened by raising multicultural issues in aspects of economic and religious diversity.